PENGETAHUAN PERAWAT BERHUBUNGAN DENGAN PELAKSANAAN DISCHARGE PLANNING DI RSUD Dr. M. HAULUSSY AMBON - Dene Fries Sumah; Ritje Andriana Nendissa (FORUM ILMIAH KESEHATAN, 2019)
Discharge planning is planning the patient's return, to provide information to patients and their families about things that need to be avoided and carried out in connection with the conditions. Discharge planning written on paper which is the purpose of patient care planning. Discharge planning can motivate patients to achieve recovery, can have an impact on shortening patient care in hospital, lowering the budget for hospital care needs, reducing recurrence rates, and allowing interventions to return plans can be done on time. This study aims to determine the relationship between nurses' knowledge and the implementation of discharge planning in Dr. M. Haulussy Ambon. This study used a cross-sectional design. The sample size of this study was 60 respondents, selected by total sampling technique. Research instruments in the form of questionnaires and observation sheets. The collected data was analyzed by Chi square test. Based on the results of the study note that respondents who had knowledge in the